FROM JOKE TO JOURNALISM: THE EVOLUTION OF MEMES IN MASS COMMUNICATION - Melati Budi Srikandi; Haggie Arranda Wahab; Latupeirissa, Jonathan Jacob Paul (al-Balagh : Jurnal Dakwah dan Komunikasi, 2024)
The emergence of memes as a prevalent form of communication in the digital age has transformed them from simple humor to influential tools shaping public opinion and societal dynamics. This study tracks memes' evolution from fundamental humor to political discourse and social mobilization in mass media. The study uses theoretical frameworks to trace memes' progression from amusing content to a major form of visual communication in the digital age. The study shows that memes have gone from amusing diversions to shaping public opinion. Mass communication relies on memes to influence public opinion, social awareness, and political outcomes. The paper discusses how memes have disrupted journalism and allowed anyone to participate in public debate through satire and critique. The study also examines the ethical issues surrounding memes in mass communication, shedding light on their potential effects. This research sheds light on memes' significant role in shaping public discourse, influencing beliefs, and engaging diverse audiences in discussions about social and political issues. By exploring the evolution of memes in mass communication, this study highlights their potential to disrupt journalism, spark public debate, and raise ethical considerations.